2013
DOI: 10.3233/jad-122278
|View full text |Cite
|
Sign up to set email alerts
|

Increased Apolipoprotein D Dimer Formation in Alzheimer's Disease Hippocampus is Associated with Lipid Conjugated Diene Levels

Abstract: Previous studies indicate that apolipoprotein D (apoD) may have a lipid antioxidant function in the brain. We have shown that apoD can reduce free radical-generating lipid hydroperoxides to inert lipid hydroxides in a reaction that involves conversion of surface exposed apoD methione-93 (Met93) residue to Met93-sulfoxide (Met93-SO). One consequence of this reaction is the formation of a stable dimerized form of apoD. As cerebral lipid peroxidation is associated with Alzheimer's disease (AD), in the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 57 publications
2
36
1
Order By: Relevance
“…Several previous studies have shown that apoD levels are up-regulated in the AD brain (Bhatia et al, 2013;Terrisse et al, 1998;Thomas et al, 2003;Thomas et al, 2001), that there is a marked increase of neuronal apoD expression in AD (Desai et al, 2005;Kalman et al, 2000), and that apoD is found in amyloid plaques (Desai et al, 2005). Three studies have also reported associations between variations in the APOD gene and AD risk (Chen et al, 2008;Desai et al, 2003;Helisalmi et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Several previous studies have shown that apoD levels are up-regulated in the AD brain (Bhatia et al, 2013;Terrisse et al, 1998;Thomas et al, 2003;Thomas et al, 2001), that there is a marked increase of neuronal apoD expression in AD (Desai et al, 2005;Kalman et al, 2000), and that apoD is found in amyloid plaques (Desai et al, 2005). Three studies have also reported associations between variations in the APOD gene and AD risk (Chen et al, 2008;Desai et al, 2003;Helisalmi et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…It is also established that apoD levels are increased in affected brain regions in Alzheimer's disease (AD) and in AD mouse models (Bhatia et al, 2013;Terrisse et al, 1998;Thomas et al, 2003;Thomas et al, 2001). Additional studies show that brain lipid peroxidation is increased during aging (Cristiano et al, 1995;Droge and Schipper, 2007), as well as in AD and AD mouse models (Abdul et al, 2008;Markesbery and Carney, 1999;Montine et al, 2007;Sayre et al, 1997;Schuessel et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…At the cellular and organismal levels, this lipocalin has been proven to have various functions: protection from oxidative stress through lipid peroxide reduction (Bajo-Graneras et al, 2011a,b;Bhatia et al, 2011Bhatia et al, , 2013Ganfornina et al, 2008), neuronal differentiation (Kosacka et al, 2010;Ruiz et al, 2013) and regeneration of damaged nerves (Ganfornina et al, 2010;Garcia-Mateo et al, 2014). However, in spite of the established link between ApoD and aging, mostly with the aging nervous system, an experimental test causally associating ApoD to mammalian longevity or brain aging is still missing.…”
Section: Introductionmentioning
confidence: 96%